RANCANG BANGUN TRAINER PRAKTIKUM PLC-HMI LAMPU LALU LINTAS DAN LAMPU FLIP-FLOP - Helmi, Arif; Rozie, Fachrul; Radwitya, Erick (Electrical Network Systems and Sources, 2024)
Design and implementation of a PLC-HMI practical trainer for traffic light and flip-flop lamp applications. The trainer aims to simulate real traffic light and flip-flop scenarios using PLC (Programmable Logic Controller) CP1L and HMI (Human Machine Interface) MT8071iP. The key objectives include ensuring the trainer functions as intended and the programs operate correctly. The design process involves integrating the CP1L PLC with the MT8071iP HMI to control traffic lights and flip-flop lamps. The PLC serves as the core controller, executing logic based on input signals and programming sequences to manage the lights' timing and states. The HMI provides a user-friendly interface for operators to monitor and interact with the system, displaying real-time status and allowing manual overrides if necessary. The practical trainer's development includes hardware integration, software programming using PLC ladder logic, and HMI configuration to establish communication and synchronization between the devices. Testing procedures ensure the trainer meets functional specifications, verifying that traffic light sequences and flip-flop operations align with expected behavior. In conclusion, the implemented PLC-HMI practical trainer successfully achieves its objectives of simulating traffic control scenarios and flip-flop lamp operations. The project underscores the importance of accurate programming and reliable hardware integration in industrial automation systems, ensuring operational efficiency and adherence to design requirements Keywords: Practical trainer, PLC (Programmable Logic Controller), HMI (Human Machine Interface), Traffic lights, Flip-flop lamps